Strengthening women’s psychosocial support through psychoeducation in the Former Argorejo Localisation Area - Pradipta Christy Pratiwi; Lukki Lukitawati; Moh. Farizqo Irvan; Chamilul Hikam Al Karim; Fikrotul Hanifah (University of Merdeka Malang, 2025)
The Argorejo karaoke district has become a popular destination for night-time leisure activities in Semarang. A study was conducted in collaboration with the Argorejo Karaoke Association (PAKAR). It was determined that specific programmes, including those utilising psychological principles, is necessary. The challenges experienced by these individuals frequently pertain to a lack of support from their social networks, profound emotional distress, and an inability to effectively cope with adversity. The psychoeducation approach was employed in a study involving 49 females who were employed as lady companions. Initially, the participants were provided with psychosocial support material. Secondly, focus groups were convened and facilitated using